Promoting empathy using design thinking in project based learning and as a classroom culture / Adila Md Hashim, Sharipah Ruzaina Syed Aris and Chan Yuen Fook. - Md Hashim, Adila; Syed Aris, Sharipah Ruzaina; Chan, Yuen Fook (2019)
This paper explores the benefits of empathy skill for school students. The encouragement of empathy skill in school was discussed in two situations: 1. Using design thinking approach for project-based learning and 2. Promoting as a classroom culture. Empathy is an act of understanding, being conscious and experiencing the feeling and thoughts of other people. It is the key to inspire social innovation and diminishing prejudice against others. Empathy skill has affected our feeling of wellbeing and human centeredness to provide an understanding of people’s needs. By integrating design thinking process in school, students will equip themselves with empathy-related skills such as communication, observation, decision-making and positive relationship with others as part of their active learning process. Adapting design thinking in project-based learning requires students to be aware and concern in exploring human-driven design which leads to user satisfaction for any problem’s solution. Empathy also has the advantage of forming a positive classroom culture and sustaining a good teacher student relationship. This paper discussed how the design thinking process can promote empathy skill during project-based learning for humanizing decision-making and the opportunity for empathy integration in the classroom to engage in positive collaboration and teamwork.